2015
DOI: 10.1186/s40068-015-0049-7
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical quality of drinking water sources in Ethiopia and its health impact: a retrospective study

Abstract: Background: This retrospective study was aimed to examine the distribution of some physicochemical parameters and its health impact in selected drinking water sources of Ethiopia. The study used 983 water samples collected from different regions of the country, and have been tasted in the Environmental Health Laboratory, Ethiopian Public Health Institute, from 2003 to 2011. The samples were collected from eight regions plus two administrative cities of the country and classified based on the source type as spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 7 publications
3
26
0
Order By: Relevance
“…In general, this study showed that more than 80% of all parameters analyzed from improved water sources (spring, tap, and well) were found within the national standards and WHO guidelines. These findings are in agreement with the previous study summarized from the same water quality database (18). However, the remaining 20% of water quality parameters collected from improved water sources which failed to meet both national standards and WHO guidelines along with above 35% of overall Ethiopian population relied on unprotected water sources reported by Ethiopian Demographic and Health Survey (11), that could threat the public health from drinking water supply.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, this study showed that more than 80% of all parameters analyzed from improved water sources (spring, tap, and well) were found within the national standards and WHO guidelines. These findings are in agreement with the previous study summarized from the same water quality database (18). However, the remaining 20% of water quality parameters collected from improved water sources which failed to meet both national standards and WHO guidelines along with above 35% of overall Ethiopian population relied on unprotected water sources reported by Ethiopian Demographic and Health Survey (11), that could threat the public health from drinking water supply.…”
Section: Discussionsupporting
confidence: 91%
“…This pH range has also been recommended by WHO guidelines for drinking water quality. However, about 25% of water samples (12% and 14% below and above the recommended boundaries, respectively) in this study didn't comply with this recommendation (Table 2), which is consistent with a similar study conducted by Alemu et al (18). So, a pH value below 6 leads to toxic nature and a pH greater than 9 turns the water taste to a bitter taste (19).…”
Section: Discussionsupporting
confidence: 86%
“…Presence of phosphates in groundwater may be attributed to natural minerals or through pollution by application of fertilizer, sewage and industrial waste (Alemu et al 2015).…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…The high levels of both phosphates and nitrates can lead to eutrophication, which increases algal growth and ultimately reduces dissolved oxygen in the water. The presence of phosphates in groundwater may be attributed to natural minerals or through pollution by application of fertilizer, sewage and industrial waste (Alemu et al 2015). The concentration of phosphate for the collected sampling sites is in the range of 0.23-1.0 mg/L which falls within the prescribed limit of WHO standards.…”
Section: Drinking Suitabilitymentioning
confidence: 79%